Babylonian Quito, miraculous law and redemptive theater: translation of the colonial market in religious images - Coronel, Valeria (Nawi, 2022)
This article analyses the rhetoric that organizes religious oratory and Virgin Mary representations in the colonial Quito baroque discourse.  The article reflects on the use of religious concepts to understand the formation of a colonial market, demographical changes and mobility, domination and power together with the formation of subjectivities framed in the discourse of Salvation, all of these under the question of catholic modernity and colonialism. The study describes how subjectivities and social transactions that emerged as result of the expansion of mercantilism are represented and regulated in the moral discourse of colonial art, religious oratory, and  moral theater exhibited in the famous Quito´s Pasion Week pageant of the XVII and early XVIII century.
Keywords: words: merchantilism; colonial paintings; modern subjectivity; baroque; Jesuits; colonial thought; catholic modernity; Quito